Innovative Technology in English Language Teaching: Enhancing Early Start in Teaching English through Zoom - Novita Mutiah Yudha; Ahmad Munir; Lies Amin Lestari; Syafi'ul Anam (Jurusan Sastra Indonesia, 2021)
Eearly start in teaching English became an ability to create successful learning by using innovative technology. The purpose of this study is to investigate an early start to learn the English using Zoom by enrolling five students to participate along with problems. The researcher gained by observation techniques, interview and uses qualitative method. The finding revealed that students are more interested while learning by Zoom. The problem was the unstable internet connection.Keyword: Innovative Technologies, Early Start in Teaching English, Zoom